2020
DOI: 10.3390/ijms21176313
|View full text |Cite
|
Sign up to set email alerts
|

GPx8 Expression in Rat Oocytes, Embryos, and Female Genital Organs During Preimplantation Period of Pregnancy

Abstract: This study aimed to detect the presence of glutathione peroxidase 8 (GPx8) in rat during preimplantation period of pregnancy. Females were killed on first (D1), third (D3), and fifth (D5) day of pregnancy. The presence of GPx8 in embryos was detected under the confocal microscope, the presence of GPx8 in genital organs was confirmed immunohistochemically, and the amount of GPx8 was determined using densitometry. We found that GPx8 is dispersed in the cytoplasm of oocytes, while after fertilization, it is conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…An intriguing moment was the detection of GPx8 in the plasma of the specimens of healthy tissue. A similar result was found during the immunohistochemical staining of rat female genital organs [47]. This could be related to the oxidative processes in the plasma [48].…”
Section: Discussionsupporting
confidence: 82%
“…An intriguing moment was the detection of GPx8 in the plasma of the specimens of healthy tissue. A similar result was found during the immunohistochemical staining of rat female genital organs [47]. This could be related to the oxidative processes in the plasma [48].…”
Section: Discussionsupporting
confidence: 82%
“…GPX8 has multifarious functions in the body, which have been illustrated in recent studies. For example, GPX8 protects against endotoxic shock ( Hsu et al, 2020 ), regulates oxidative stress during pregnancy ( Mihalik et al, 2020 ), and maintains microsomal membrane lipid homeostasis in HELA cells ( Bosello-Travain et al, 2020 ). In addition, GPX8 has also been found to promote tumor progression through multiple important pathways, such as Wnt and JAK/STAT3 ( Chen et al, 2020 ; Khatib et al, 2020 ; Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies by Shivalingappa et al [90] suggested multifunctional roles of RBM47 in processes such as RNA editing and transcriptional activation during blastocyst development. In a rat experiment by Mihalik et al [91], GPX8 was observed throughout the preimplantation period from unfertilized oocytes to blastocysts. Notably, GPX8 was detected in the ovary, uterine tube, and uterus of the mother, with the highest protein levels observed on day one of pregnancy, which gradually declined thereafter.…”
Section: Candidate Gene Functions Associated With Naipcmentioning
confidence: 94%